Nonlinear studies of graphene oxide and its application to moisture detection in transformer oil using D-shaped optical fibre - Zakaria, Rozalina; Mezher, Mezher H.; Zahid, Ali Z. Ghazi; Rohizat, Nurul Syazwani; Patel, Shobhit K.; Amiri, Iraj Sadegh (Taylor & Francis, 2020)
This paper reports nonlinear optical response studies of thin layers using graphene oxide (GO) and their performance for detecting water content in transformer oil using three sets of approaches. The sensor performance is evaluated based on bare optical fibre, D-shape optical fibre integrated with GO and the effects of the covering device with polydimethylsiloxane (PDMS). The improvement of this study is to ensure the stability of the recorded signal. The nonlinear optical response of the prepared dispersion was explored using the Z-scan technique with an 800 nm continuous wave laser beam. Taking advantage of the graphene-induced evanescent field using D-shape optical fibre with PDMS covers on the device can give high sensitivity and good stability for water dissolved in the oil at 1550 nm. We measured fluctuations in transmitted light associated with varying water contents ranging from 16 to 38 ppm. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.